2006
DOI: 10.1080/13645700600640774
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative and interventional MRI: Recommendations for a safe environment

Abstract: In this paper we report on current experience and review magnetic resonance safety protocols and literature in order to define practices surrounding MRI-guided interventional and surgical procedures. Direct experience, the American College of Radiology White paper on MR Safety, and various other sources are summarized. Additional recommendations for interventional and surgical MRI-guided procedures cover suite location/layout, accessibility, safety policy, personnel training, and MRI compatibility issues. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 38 publications
0
22
0
1
Order By: Relevance
“…MR has many advantages such as multiplanar imaging without registration efforts (very useful for subdiaphragmal lesions) and registration errors, may get advantage of hepatospecific contrast agents and has the highest liver-tumour contrast compared to CT and US and has no ionizing radiation (13). MR, however is expensive and requires compatible equipment, access may be limited and needs experience, and may be currently only useful for lesions not accessible by other methods (14)(15). Paired-point registration calculates the geometrical transformation that best aligns corresponding points in image and patient space, respectively (12,16).…”
Section: Discussionmentioning
confidence: 98%
“…MR has many advantages such as multiplanar imaging without registration efforts (very useful for subdiaphragmal lesions) and registration errors, may get advantage of hepatospecific contrast agents and has the highest liver-tumour contrast compared to CT and US and has no ionizing radiation (13). MR, however is expensive and requires compatible equipment, access may be limited and needs experience, and may be currently only useful for lesions not accessible by other methods (14)(15). Paired-point registration calculates the geometrical transformation that best aligns corresponding points in image and patient space, respectively (12,16).…”
Section: Discussionmentioning
confidence: 98%
“…Although, the preparation time for MRI might be potentially longer than in fluoroscopy (as it includes the correct placement of the radiofrequency coil), recent studies have shown how acceptable times can be achieved [23]. In this regard, appropriate training of intervention team plays an essential role [24]. When using the iPad as a visualisation device, times were slightly longer in the case of RTiPadBT configuration [4.25 (0.45) min for treatment phase] but shorter in the case of GEiPadBT.…”
Section: Discussionmentioning
confidence: 99%
“…A narrow burr hole and the noise lead to low surgical comfort. Furthermore, many safety issues must be taken into account regarding heating and "missile" effects (7,9,14,23,24). To reduce heating risk for DBS electrodes, a very low head-specific absorption rate level (Ͻ0.1 W/kg) is recommended by the manufacturer, thus resulting in poor image quality.…”
Section: General Experiencesmentioning
confidence: 99%